(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
There has been an increment of Malaysian internet users in recent years. Younger users, specifically Generation Z, also named the internet generation, are considered the category that actively participates and shares content through social media or group messaging. When the world becomes more interconnected, the adoption of technological gadgets is increasing. It changes the identity of the audience from passive to active recipient while processing the message. In fact, utilizing digital gadgets and managing information competently are a set of skills that are essential for every individual. However, fundamental understanding of digital media literacy remains unclear. Therefore, this paper outlines the concept of digital media literacy from various literature. The discussion is based on five competencies, namely (i) (i) competence of access, (ii) analysis and evaluation, (iii) creation, (iv) reflection, and (v) action.Digital Media Literacy This study aims to provide a guideline for educators by ifying the issues that related to digital media literacy and competencies among students while conducting the class. Besides, further information on the existing frameworks of digital literacy will also be elaborated and refined.